1990
DOI: 10.3354/dao009045
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of midgut gland-cells of Penaeus monodon postlarvae after Leucaena leucocephala feeding

Abstract: ABSTRACT. Leucaena leucocephala, one of the promising feed sources in aquaculture of tropical regions, induces drastic pathological alterations in the midgut gland ( = hepatopancreas) cells of Penaeus monodon postlarvae. After 28 d feedng on a formulated diet containing Leucaena wlth natural mimosine content, the most severely affected cell type is the R-cell, followed by F-cells B-cells are only rarely pathologically changed. Artificial reduction of mimosine content prior to &et formulation results in less se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The most prominent feature of HBL cytopathology is the depression of individual, bacteria-contacted microvilli. Such a peculiar kind of bacterial attachment has not previously been reported for aquatic animals (Johnson 1983, Kinne 1983-1990). Adhesion of bacteria to surface structures of target cells is often a prerequisite of their pathogenicity (Huq et al 1986, Yamamoto & Yokota 1989.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The most prominent feature of HBL cytopathology is the depression of individual, bacteria-contacted microvilli. Such a peculiar kind of bacterial attachment has not previously been reported for aquatic animals (Johnson 1983, Kinne 1983-1990). Adhesion of bacteria to surface structures of target cells is often a prerequisite of their pathogenicity (Huq et al 1986, Yamamoto & Yokota 1989.…”
mentioning
confidence: 88%
“…(2) The observed discharge also does not reflect extrusion of R-cells and F-cells damaged by premature aging, chemicals, viruses, etc., because in such cells the organelles would be considerably transformed prior to rupture of the microvillous border (Vogt 1990). In HBL, however, the bacteria-contacted microvillous borders disintegrated before there was any obvious lesi.on, of the cell organelles (Fig.…”
mentioning
confidence: 99%
“…F cells are implicated in the synthesis and secretion of digestive enzymes and R cells store the lipids and glycogen, and are also implicated in the detoxification processes (Vogt and Quinitio, 1994;Icely and Nott, 1992;Johnston et al, 1998). The profound damages observed in these cells, particularly in R cells, such as nuclear retraction, pyknosis, cytoplasmic vacuolization, and cytoplasmolysis largely followed the scheme given by Vogt (1990) and Trump et al (1981) for this stage of necrosis. It has been suggested that Rcells are the most sensitive to metabolic and environmental changes such as starvation, salinity and pollutants (Storch and Anger, 1983;Masson, 2001;Vogt, 1987;Vogt and Quinitio, 1994).…”
Section: Discussionmentioning
confidence: 66%
“…In P. argentinus, the degenerative desquamation is a usual periodic event during the moulting cycle (Sousa and Petriella, 2000;2001). However, in this prawn, like in P. monodon (Vogt, 1990), A. longinaris (Masson, 2001), and P. muelleri (Cuartas et al, 2003), the increased desquamation produced by different stressors results in a high rate of cell loss that does not make possible the restitution of the damage tissue. This has been mentioned for Litopenaeus vannamei, L. stylirostris and Farfantepenaeus californiensis (Lightner and Redman, 1994) infected by the NHP virus, in which necrosis foci with important haemocytic infiltration were also characteristic.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation